Assessment of performance and quality indices of glutinous rice under different drying methods - Jimoh, Kabiru Ayobami; Hashim, Norhashila; Shamsudin, Rosnah; Che Man, Hasfalina; Jahari, Mahirah (Elsevier Ltd, 2025)
Drying is an energy-intensive process that prolongs grain shelf life and reduces postharvest losses from moisture-induced spoilage. Stakeholders in the grain supply chain have diverse interests regarding grain quality, energy efficiency, environmental impact, and the economic performance of the drying process. Therefore, the processing industries are highly concerned with the selection of most appropriate drying method for grain. This study experimentally evaluated various performance indices of glutinous rice under different drying methods, including hot air box drying (BD: 50 °C−70 °C), convective oven drying (COD: 50 °C−70 °C), infrared drying (IRD, at 200 W/m2−600 W/m2) and microwave drying (MWD: 1000 W/kg−3000 W/kg). The results demonstrated that MWD outperformed other methods in terms of drying kinetics, with an average production rate of ∼1.65, ∼2.02, and ∼2.37 times higher than IRD, BD, and COD, respectively. Also, MWD has the most promising economic performance with least environmental impact which was ∼28.64, ∼16.31 and ∼2.21 times lower than BD, COD and IRD, respectively. Despite the excellent drying efficiency, sustainability indices, energy and exergy efficiency exhibited by IRD and MWD compared to other methods, they are still characterized with low milling quality and macronutrients retention in the final product. Therefore, while IRD and MWD excel in drying efficiency and sustainability, they need further quality improvements before widespread industrial use.